2022
DOI: 10.1002/jcv2.12124
|View full text |Cite
|
Sign up to set email alerts
|

The network structure of posttraumatic stress symptoms in war‐affected children and adolescents

Abstract: Background: It is unclear whether findings from previous network analyses of posttraumatic stress disorder (PTSD) symptoms among children and adolescents are generalizable to youth living in war-torn settings and whether there are differences in the structure and connectivity of symptoms between children and adolescents. This study examined the network structure of PTSD symptoms in a sample of war-affected youth and compared the symptom networks of children and adolescents. Methods: The overall sample comprise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 44 publications
3
5
0
Order By: Relevance
“…Consistent with the child networks, this subscale had the highest strength centrality for adolescents, in addition to emotion dysregulation, behavioral dysregulation, and those related to negative self-identity (low confidence and negative self-image). The centrality of the emotion dysregulation and negative self-concept symptoms is consistent with previous network studies of PTSD symptoms in children and adolescents (Bartels et al, 2019, De Haan et al, 2020Scharpf et al, 2022). Together with the importance of attachment dysregulation symptoms, these patterns support the transdiagnostic model of developmental mechanisms that explain the link between childhood trauma and psychopathology (McLaughlin et al, 2020) and is consistent with the conceptualization of developmental trauma disorder (DTD; van der Kolk et al, 2009).…”
Section: Network Composition Of Complex Trauma Symptomatologysupporting
confidence: 85%
See 2 more Smart Citations
“…Consistent with the child networks, this subscale had the highest strength centrality for adolescents, in addition to emotion dysregulation, behavioral dysregulation, and those related to negative self-identity (low confidence and negative self-image). The centrality of the emotion dysregulation and negative self-concept symptoms is consistent with previous network studies of PTSD symptoms in children and adolescents (Bartels et al, 2019, De Haan et al, 2020Scharpf et al, 2022). Together with the importance of attachment dysregulation symptoms, these patterns support the transdiagnostic model of developmental mechanisms that explain the link between childhood trauma and psychopathology (McLaughlin et al, 2020) and is consistent with the conceptualization of developmental trauma disorder (DTD; van der Kolk et al, 2009).…”
Section: Network Composition Of Complex Trauma Symptomatologysupporting
confidence: 85%
“…De Haan et al (2020) also investigated PTSD and depression symptoms in an international sample of children and youth, finding re-experiencingrelated PTSD symptoms and impaired concentration in depression to be the most central. Additionally, Scharpf et al (2022) examined PTSD symptom networks in a sample of waraffected children and adolescents from across six countries. Re-experiencing and avoidance were most strongly connected to other symptoms in the full sample, as well as child-and adolescentspecific networks.…”
Section: Child and Adolescent Trauma Symptom Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…The centrality indices in all networks underscore the primacy of the attachment-specific symptoms, negative self-concept, and emotional dysregulation, irrespective of developmental stage and gender. The (Bartels et al, 2019;De Haan et al, 2020;Scharpf et al, 2022). Together with the importance of attachment dysregulation symptoms, these patterns support the transdiagnostic model of developmental mechanisms that explain the link between childhood trauma and psychopathology (McLaughlin et al, 2020) and is consistent with the conceptualization of developmental trauma disorder (DTD; van der Kolk et al, 2009).…”
Section: Network Composition Of Complex Trauma Symptomatologysupporting
confidence: 63%
“…For example, Elliott et al (2020) found that nodes central to pretreatment anorexia nervosa symptom networks were prognostic indicators for recovery. Systematic reviews of symptom network analyses show that this statistical approach has been widely applied as a technique for better understanding symptom relationships across adults (Contreras et al, 2019; McNally et al, 2022; Robinaugh et al, 2020) and youth (Anderson et al, 2015; Boschloo et al, 2016; Cervin et al, 2020; Goldschmidt et al, 2018; Grassie et al, 2022; Heeren & McNally, 2016; Martel et al, 2016; Russell et al, 2017; Ruzzano et al, 2015; Scharpf et al, 2023; Schweren et al, 2018; Smith et al, 2017). However, while the utility of symptom network analyses in driving clinical research and intervention-related outputs is exciting, more research are needed to support the use of network analysis results in clinical practice (Bringmann et al, 2022; Castro et al, 2019).…”
Section: Symptom Network Analysismentioning
confidence: 99%